Hubungan Antara Citra Tubuh Dengan Penerimaan Diri Pada Remaja Putri Pengguna Media Sosial Instagram - Jyoti Sara, I Gusti Ayu Savitri; Swandi, Ni Luh Indah Desira (Jurnal Ilmiah Wahana Pendidikan, 2025)
The emergence of the term “body goals” on Instagram certainly makes body shape a matter that must be considered by most individuals, including teenagers, especially adolescent girls. Adolescent girls who are experiencing physical changes in themselves, of course, must be accepted by adolescent girls. This study aims to see if there is a relationship between body image and self-acceptance in adolescent girls who use Instagram. This study uses quantitative methods and uses incidental sampling techniques involving 103 respondents with an age range of 16 years to 19 years. Data collection was carried out by distributing questionnaires online using the Body Image Scale and Self-Acceptance Scale. Data were analyzed using Spearman's Rho Correlation Test. The results showed that there was a significant relationship between aspects of appearance evaluation, satisfaction with body parts, anxiety about being fat, and body categorization with self-acceptance variables (p < 0.05). Meanwhile, there is no significant relationship between aspects of appearance orientation and self-acceptance variables.